Тарози тошларининг шаклланиш тарихи (SCIENCE and SOCIETY, 2022)
This article talks about scales, the history of the creation of scales and their refinement. The role and importance of scales in everyday life, engineering, technology and other industries has been studied, and the history of its formation has been widely discussed.